The Influence of Financial Literacy, Financial Attitudes, and Lifestyle on the Financial Behavior of University Students in Yogyakarta (A Case Study of Generation Z) - , Megawati; Moin, Abdul (Journal of Business and Management Review, 2024)
Research Aims: This study aims to examine the influence of financial literacy, financial attitudes, and lifestyle on the financial behavior of students in Yogyakarta. Design/methodology/approach: This study employs a quantitative research method using the SEM-PLS approach. Data were collected through questionnaires with numerical and textual responses. The target population consists of university students in Yogyakarta, with a non-probability sampling method and purposive sampling technique utilized. The sample size was determined 250 respondents. Data analysis was conducted using SmartPLS 3.0. Research Findings: Financial literacy enhances financial behavior, with higher literacy levels leading to better financial management among students and fostering financial independence. Positive financial attitudes also improve financial behavior by promoting effective budgeting and informed decision-making. Additionally, a positive lifestyle aids financial management, as students who embrace healthy lifestyles are more aware of saving and investing, cultivating good financial habits for the future. Theoretical Contribution/Originality: This study contributes both academically and practically; academically, it serves as a foundation for further research in financial literacy, suggesting the inclusion of additional variables, such as digital finance and students' understanding of loans and debt, as well as psychological, social, and cultural aspects.